Plan de comercialización para el local comercial de comida “Asados Bacu” en la ciudad de Macas, provincia de Morona Santiago. - Barba Cuji, Damaris Jhomira (2025)
The commercial food store "Asados Bacu" lacks strategies and resources in terms of marketing, which is why I did the following work: Marketing plan for the commercial food store "Asados Bacu" in the city of Macas, province of Morona Santiago. The main objective of the research focuses on determining the strategies and tactics to establish a marketing plan, among which social networks, primarily "Facebook," have a schedule of marketing tactics to penetrate the market and, in the minds of consumers, the name "Asados Bacu."Asfor the research methodology, 333 surveys were developed of the local population of Macas; in the same way, an interview was conducted with the regional manager for background knowledge was also based on the literature on similar topics, so these scientific articles were reviewed. An analysis of the current situation in the Macas population was observed through the surveys carried out. The consumption of the food offered has been done traditionally to make known the trajectory that the business has had for more than 25 years, not only in an ambulatory way with the business beginning but in an entrepreneurial way. That is to say, the recognition of the name "Asados Bacu." Business proposal. We presented a plan of activities and tactics for brand penetration through posters and flyers. All this is arranged with a schedule of activities for the year and according to the consumer's needs. Also, it is essential to have a business philosophy. Expected results with an investment of $ 811.00 in terms of advertising material and promotion through social networks, especially "Facebook" because it is the most used network and easily accessible to the consumer, and thus builds customer loyalty and manages a record of customers resolving concerns and suggestions. Conclusions and recommendations Through the implementation of objectives and marketing strategies, among which we must advertise more frequently on the Facebook page, having a plan of advertising material designed for a whole year will facilitate that through social networks will be more open to market penetration.